The Important Significance of Introducing Students to Artists' Creations in Circle Classes (Ural Tansikbaev) - Alimjanovna, Yusupova Shoxista (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
In this article, the opportunities given to young people and the important role of our talents, the importance of visual arts in human life. The head of the fine art club is informed about the search for himself, the first step of creativity, the important aspects of the work of artists in the use of new technologies in their training. Analysis of the main laws and rules of nature painting in fine art classes and the life and work of the artist Ural Tansikbaev, who created in this genre in Uzbekistan. Opinions were expressed about the importance of the works of famous artists in the lives of our youth. In the article, the important role of developing the aesthetic taste of young people through the genre of landscape in fine art classes. Information about the influence of the landscape genre on human life has been given.